Penyuluhan Pentingnya Mengenal Jenis Golongan Darah Bagi Kader dan Warga di Kelurahan Karikil Mangkubumi Tasikmalaya - Meri Meri; Rudy Hidana; Dewi Peti Virgianti; Korry Novitriani (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2020)
Each individual's blood group is of different types, some of which are ABO and rhesus bloodÂ groups[ 1]. Choosing a blood type for blood transfusion needs, should be known by everyone. ThisÂ is very important in saving a person's life, so in determining the type of blood must be precise. InÂ this activity, especially the cadres, it is necessary to know the type of blood type. Cadres have anÂ indirect role in contributing to improving public health. The purpose of this community serviceÂ activity is to provide additional knowledge for cadres, with counseling methods on the importanceÂ of knowing the type of blood group, both ABO and rhesus blood group types. The result of thisÂ activity is the increasing knowledge of cadres about knowledge in knowing the type of blood groupÂ and rhesus. Through this counseling is intended so that cadres understand the type of blood groupÂ sought when helping people who are in need, one example is to help find blood with the appropriateÂ blood type or suitable to be given at the time of transfusion. In conclusion, all cadres or counselingparticipants understand about the importance of knowing the type of group.